Identification of cross-reactive vaccine antigen candidates in Gram-positive ESKAPE pathogens through subtractive proteome analysis using opsonic sera - Océane Sadones; Eliza Kramarska; Maite Sainz-Mejías; Rita Berisio; Johannes Huebner; Siobhán McClean; Felipe Romero-Saavedra (PLoS ONE, 2025)
The Gram-positive pathogens of the ESKAPE group, Enterococcus faecium, and Staphylococcus aureus , are well-known to pose a serious risk to human health because of their high virulence and numerous drug resistances. To narrow down the list of previously identified promising protein vaccine candidates, a combination of several antigen discovery approaches was performed, in particular a “false positive analysis” of peptides generated by trypsin shaving with a subtractive proteome analysis. The final list of nine potential antigens included AdcA au , a protein performing the same function as AdcA fm , an already discovered antigen in enterococci. Bioinformatic analyses revealed that AdcA au and AdcA fm share a sequence identity of 41.2% and that the conserved regions present a high antigenicity. AdcA au was selected for further investigation and the results reported in this manuscript demonstrate the opsonic properties of AdcA au -specific antibodies against the Staphylococcus aureus strain MW2, as well as their cross-binding and cross-opsonic activity against several S. aureus, E. faecium , and E. faecalis strains. The experimental design revealed several promising vaccine candidates, including the newly identified S. aureus antigen, AdcA au . The study shows its potential as a vaccine candidate to prevent infections by dangerous Gram-positive ESKAPE pathogens.